Pengaruh Aset Pajak Tangguhan Dan Penghindaran Pajak Terhadap Manajemen Laba Pada Perusahaan Manufaktur YangTerdaftar Di Bursa Efek IndonesiaTahun 2022 - Nurjaya, Angelia; Hendri, Nedi; Padwa Sari, Gustin (Universitas Muhammadiyah Metro, 2025)
This research aims to examine the effect of deferred tax assets and tax avoidance on profit management in manufacturing companies listed on the Indonesian Stock Exchange in 2022. The population in this study is 180 manufacturing companies listed on the Indonesian Stock Exchange. The sampling technique used was purposive sampling and the samples used were 50 companies. Testing techniques consist of Descriptive Statistical Analysis, Multicollinearity Test, Heteroscedasticity Test, Autocorrelation Test, t Test, F Test, and Coefficient of Determination Test. The results of this research show 1). Deferred Tax Assets have no effect on earnings management. 2) Tax avoidance influences earnings management. 3) The results of the F test state that together the variables Deferred Tax Assets and Tax Avoidance influence earnings management.